The Effectiveness of Reflection Learning Method to Increase the First Grade Students’ Writing Skill of SMA Negeri 2 Sungguminasa Gowa Regency - Musdalifah Musdalifah (Universitas Muhammadiyah Enrekang, 2018)
This research consisted of two objectives research, first objective research that was to find out the students’ increased of content of writing recount text by using reflection learning method at the first grade students of SMA Negeri 2 Sungguminasa Gowa Regency, and second objective research that was to find out the students’ increased of organization of writing recount text by using reflection learning method at the first grade students of SMA Negeri 2 Sungguminasa Gowa Regency. There were of assessment focused on the skill of students to write a recount text from content which consisted of unity, and completeness; organization which consisted of coherence, and spatial order; and generic structures which consisted of orientation, events, and reorientation. This research applied Classroom Action Research (CAR) design which divided into two cycles (cycle I and cycle II) and consisted of four stages or phases (planning, implementation of action, observation, and reflection). The subject of this research that was students of class X which consisted of 33 students. The instrument of this research that was writing test which it used recount text. The test would be used in the last item of every cycle. Moreover, based on the students’ score in cycle I and cycle II, it showed that the score of students is increased from the standard score 7.00 with the significant increased 47.27 %.